(untitled) (Reflection and Critique Law Magazine, 2022)
The increase in domestic violence against women in Brazil, its recurrence during the social isolation of the COVID-19 pandemic, the absence of effective public policies that address issues around this domestic and gender violence in the midst of a Brazil still with traces of a patriarchal model and under Law 11.340/2006. However, it is necessary to demonstrate domestic violence and its recurrence in Brazil during pandemic and to understand the importance of Law 11.340/2006 in our legal system. And to guide the research, the strategy used was: to identify the causes of domestic violence against women in Brazil, present statistical data on domestic violence against women and its recurrence during the COVID-19 pandemic in Brazil, discuss about the Law 11.340/2006 and its effects on the legal system. Its relevance is in the need to expose the numbers of domestic violence against women and its recurrence, so that public policies are developed and consequently applied to punish and educate the aggressors. The present research was characterized as an integrative exploratory review. To this end, we used articles, document analysis, available in the Capes Periodicals and Scielo Virtual Library electronic databases, using the descriptors "domestic violence", "violence against women", "domestic violence during the pandemic" and specialized book About the subject. Given the data obtained, we realize that domestic violence against women in Brazil occurs predominantly by their ex-partners and has as main reason the separation, during the confinement of the pandemic, such aggressions occurred by fathers, mothers, brothers and companions.